When Corruption is a Response to Export Instability - Joël Cariolle (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
This paper is an empirical study on the effects of export instability on corruption, in developed and developing countries. We consider that corrupt transactions may arise from the necessity to protect against the detrimental effects of income fluctuations on welfare. We assume that export instability may have ex post and ex ante effects on corruption, resulting from agent's experience and perception of export fluctuations, respectively. We conduct empirical estimations of these effects using measures of volatility based on the standard deviation and the skewness of the distribution of exports around their trend. On the one hand, fixed effect, instrumental variable (IV) and system-Generalized Method of Moments estimations are conducted on a panel of 68 developed and developing countries covering the period 1985-2005, using data on corruption perceptions taken from the International Country Risk Guide. On the other hand, we run comparable Ordinary Least Square and IV cross-section estimations on a sample of more than 9000 firms clustered in 23 developing countries, using data on bribes paid by firms drawn from the World Bank Enterprise Surveys.Mise à jour Avril 2013.
Keywords: D10; O11; O12; O17; 330